2008
DOI: 10.1111/j.1745-5871.2008.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Value of Australian Tropical Rivers

Abstract: Until recently the objectives of tropical river management were narrowly construed: the development imperative drove resource policy. During recent decades, community attitudes to river and water management have changed considerably and the national program of water reform, the National Water Initiative, is accelerating alterations to the way that water is used, managed and priced. A broader range of values and imperatives is now influencing water resource management policy. Not least is the concern over the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…This is in line with other Australian and international studies that have identified water uses and values (e.g. Barraqué et al 2004;Davis 2006;Drewry et al 2008;Jackson et al 2008), indicating a growing societal awareness of the contribution made by rivers to human well-being and cultural identity.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This is in line with other Australian and international studies that have identified water uses and values (e.g. Barraqué et al 2004;Davis 2006;Drewry et al 2008;Jackson et al 2008), indicating a growing societal awareness of the contribution made by rivers to human well-being and cultural identity.…”
Section: Discussionsupporting
confidence: 73%
“…Although at international and national levels, water management paradigms change from technical to more ecological approaches, real change in management practices is not guaranteed because water is still allocated primarily to activities that promise clear and quantifiable economic benefits, such as hydropower generation or irrigation for agriculture (Pahl-Wostl 2006;Jackson et al 2008). However, this may be changing with, for example, the introduction of payments for ecosystem services, such as the planting of native vegetation along rivers and creeks on private land.…”
Section: Consumptive V Non-consumptive Usesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ellis, 1986;Roesner et al, 2001;Shuster et al, 2005;Walsh et al, 2005;Fletcher and Deletic, 2006) and contemporary research has identified a much broader range of societal values associated with urban waterways in relation to aesthetics, amenity, recreation, tourism, economic development, intrinsic ecological health, heritage and indigenous values (see e.g. Takahasi and Uitto, 2004;Jackson, 2006;Jackson et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Reser and Bentrupperbäumer (2005:129) explain values as more "central," "deeply considered," and "strongly held" than attitudes. Values underpin decisions and behavior (Satterfield 2001), thus studying values can provide insight into people's differing viewpoints about how environment resources should be used, managed (Jackson et al 2008), and experienced. Although a study of mental models aims to elicit people's understanding of how environmental systems function, a study of values can tap into the moral and less tangible aspects of people's cognition.…”
Section: Introductionmentioning
confidence: 99%